Gasochromic Performance of WO3-nanorod Thin Films Fabricated with an ArF Excimer Laser - Yaacob, M. H.; Ou, J. Z.; Wlodarski, W.; Kim, C. S.; Lee, J. Y.; Kim, Y. H.; Oh, C. M.; Dhakal, K. P.; Kim, J. Y.; Kang, J. H. (KOREAN PHYSICAL SOC, 2012)
Thin films with tungsten trioxide (WO3) nanorods were fabricated by using an ArF pulsed laser deposition system. Because the ArF excimer laser operates at a very short wavelength of 193 nm, short enough to expect strong absorption of the photons in the semiconductor oxide targets, and because the clusters incoming to the substrates have high momentum, we could build thin films with good surface morphology. Highly homogeneous arrays of nanorods with sizes mostly in the range of 30 - 40 nm were observed. The absorbance response towards hydrogen (H-2) gas was investigated for a WO3 film coated with 25-angstrom-thick palladium (Pd). The Pd/WO3-nanorod thin films exhibited excellent gasochromic response when measured in the visible-NIR range (400 - 1000 nm). As low as 0.06% H-2 concentration was clearly sensed. A significant reversible absorbance change and fast recovery (<2 min) were observed when the films were exposed to H-2 at different concentrations.
Keywords: TUNGSTEN TRIOXIDE; WO3; OXIDE; RAMAN